Error Identification of Written Discourses of English Major Students : An Underpinning for a Program Study - Panolong, Kara S. (Asia Pacific Higher Education Research Journal (APHERJ), 2014)
Error analysis has long been employed to determine how far the learners have progressed toward their final goal. In this study commonly committed grammatical errors of English major students wereinvestigated. Further, gender, language spoken at home/first language, reading material preferences, and attitudes toward writing were correlated to students’ errors, classified into morphological, syntactic and lexical using Hendrickson’s Model. Frequency count, percentage, rank and weighted mean, Friedman test and ANOVA were used to treat the data. Most common errors occurred in verb forms, misused/omitted preposition and misused/ omitted verb. The variables did not reflect any bearing on the errors. Implications for a program of study for these kinds of learners were also discussed.